Food, Pregnancy & Me: Exploring food insecurity in pregnancy in the UK to inform future public health intervention needs-A mixed-methods study protocol. - Kiya L Hurley; Kate Jolly; Heather Brown; Steph Scott; Zainab Akhter; Eleanor Dyer; Giang Nguyen; Amelia A Lake; Christine Möller-Christensen; Nicola Flint; Angela Baker; Kerry Brennan-Tovey; et al. (PLoS ONE)
Introduction There are several known risks relating to poor nutrition during pregnancy, including the development of complications and poor birth outcomes. While food insecurity is associated with poorer nutrition, data on the prevalence and severity of food insecurity in pregnancy in the UK is lacking. This study aims to explore the prevalence, experiences and health impact of food insecurity in pregnancy in England to develop strategic recommendations for intervention strategies. Methods and analysis Food, Pregnancy & Me is an observational, multi-method study. Questionnaires exploring diet quality, food security, mental health, and other health behaviours will be distributed to all women and pregnant people in their third trimester in two NHS Trusts in England (North East and West Midlands). Returned questionnaires (n=605) will be linked to routine maternal and birth outcome data and pseudo-anonymised. We will estimate the prevalence of food insecurity in pregnancy in these locations, associations with diet quality, maternal mental health, and pregnancy outcomes (e.g., pre-term birth, pre-eclampsia, gestational diabetes). Qualitative interviews (n=40) with participants identified as having experienced food insecurity will explore their lived experience, support received, and recommendations for additional support needs. Through a series of co-production workshops with local and national system shapers and experts by lived experience, we will use the data gathered to produce strategic recommendations for intervention with pregnant women and people facing food insecurity. We will then explore the potential costs and benefits of implementing the proposed recommendations. Ethics and dissemination Ethical approval was obtained from Newcastle and North Tyneside 1 NHS Research Ethics Committee (24/NE/0027). Findings will be disseminated to key national and local system shapers and policy makers, advocacy groups, and the public through reports, presentations, the media and open access publications. Study registration number ISRCTN16655955.